Implementation of Student Facilitator and Explaining (SFE) Strategies in Islamic Education Learning - Fauzi, Imron; Sabila, Linda Sansas; Sukrillah, Muhammad Khizam; Rachmawati, Siti Amalia (Journal of Islamic Education Research, 2022)
The Student Facilitator and Explaining are learning strategies in which the teacher can present or demonstrate the material in front of students and then allow them to explain to their friends. The Islamic Religious Education teacher at Mahfilud Duror II Vocational School saw students' lack of enthusiasm to participate in learning. The Islamic Religious Education Teacher used the Student Facilitator and Explaining strategy because he felt this strategy was easier to solve the student's problems and was under the learning objectives. The purpose of implementing the Student Facilitator and Explaining is to make students more active and to practice public speaking for students. The research context discusses how to plan, implement, and evaluate the Student Facilitator and Explaining in learning Islamic Religious Education at Mahfilud Duror II Vocational School. Strategy planning Student Facilitator and Explaining in Islamic education learning: syllabus, lesson plans, and worksheets. (2) Implementation of the Student Facilitator and Explaining in Islamic education learning, which is related to the steps for implementing the Student Facilitator and Explaining in education Islamic learning following the preparation of lesson plans, namely preliminary activities, core activities, and closing activities. Related the obstacles in implementing the Student Facilitator and Explaining in Islamic education learning are the need for more learning resources, time allocation, and student learning motivation. (3) Evaluation of the Student Facilitator and Explaining in education Islamic learning, namely attitude evaluation, namely self-assessment, peer-to-peer, and observation techniques; evaluation of knowledge using written tests, namely multiple choice and descriptions, and evaluation of skills in the form of projects.